HUBUNGAN PENGGUNAAN GAWAI DAN SIKAP ORANG TUA DENGAN PERKEMBANGAN ANAK USIA 6 TAHUN DI TKIT NURUL IMAN DAN TK AISYIYAH 32 KELURAHAN SRENGSENG SAWAH - Kharisma Ekva Nanda, (2021)
The pandemic situation created a big change in the world of education, learning process in Indonesia turned into an online learning model with gadgets that made the use of gadgets in children increase. The online learning model or BDR system makes parents the main supervisors who support children's learning by using gadgets, including children aged 6 years where children are in transition to a wider scope of education, namely Elementary School (SD). This study aims to analyze the relationship between gadget usage and parental attitudes with the development of children aged 6 years at TKIT Nurul Iman and TK Aisyiyah 32, Srengseng Sawah. This research uses a correlation study with a cross-sectional, and a total sampling technique of 38 respondents. The results of this study found that there was a relationship between gadget usage and child development with p-value<α (0.047<0.05) and there was no relationship between parents attitudes towards the development of children aged 6 years with p-value>α (0.254>0.05). This research implies that gadget usage in children is related to the development of children aged 6 years, it's necessary to educate parents from educators to pay attention to the ideal gadget usage in children to support child development.